Impact of the hypoxic microenvironment on spermatogonial stem cells in culture - Gille, A. S.; Givelet, M.; Pehlic, D.; Lapoujade, C.; Lassalle, B.; Barroca, V.; Bemelmans, A. P.; Borderie, D.; Moison, D.; Livera, G.; Gauthier, L. R.; Boussin, F. D.; et al. (Frontiers in Cell and Developmental Biology, 2024)
The stem cell niche plays a crucial role in the decision to either self-renew or differentiate. Recent observations lead to the hypothesis that O2 supply by blood and local O2 tension could be key components of the testicular niche of spermatogonial stem cells (SSCs).In this study, we investigated the impact of different hypoxic conditions (3.5%, 1%, and 0.1% O2 tension) on murine and human SSCs in culture. We observed a deleterious effect of severe hypoxia (1% O2 and 0.1% O2) on the capacity of murine SSCs to form germ cell clusters when plated at low density. Severe effects on SSCs proliferation occur at an O2 tension ≤1%. and hypoxia was shown to induce a slight differentiation bias under 1% and 0.1% O2 conditions. Exposure to hypoxia did not appear to change the mitochondrial mass and the potential of membrane of mitochondria in SSCs, but induced the generation of mitochondrial ROS at 3.5 % and 1% O2. In 3.5% O2 conditions, the capacity of SSCs to form colonies was maintained at the level of 21% O2 at low cell density, but it was impossible to amplify and maintain stem cell number in high cell density culture. In addition, we observed that 3.5% hypoxia did not improve the maintenance and propagation of human SSCs. Finally, our data tend to show that the transcription factors HIF-1α and HIF-2α are not involved in the SSCs cell autonomous response to hypoxia.